DIRECTIONS OF CHANGES OF GRAINS PRODUCTION IN POLAND - Bogusława Jaśkiewicz; Alicja Sułek (Annals of the Polish Association of Agricultural and Agribusiness Economists)
The aim of this study was to present changes in the tendency of the cereals production in Poland. Asa source material for this analysis, statistical data from GUS (1950-2015) were used. In the analyzedperiod, the expansion of the cultivation of wheat and triticale at the expense of rye and oats. The areasown cereal mixtures and barley remains at a similar level. Yields of individual cereal species increasedthe basic direction of the grain distribution is the use of fodder. It is becoming increasingly important asthe use of grain for industrial purposes and decreased consumption purposes and grazing.